Effects of Centralizing Acute Stroke Services on Stroke Care Provision in Two Large Metropolitan Areas in England. Issue 8 (August 2015) - Ramsay, Angus I.G.; Morris, Stephen; Hoffman, Alex; Hunter, Rachael M.; Boaden, Ruth; McKevitt, Christopher; Perry, Catherine; Pursani, Nanik; Rudd, Anthony G.; Turner, Simon J.; Tyrrell, Pippa J.; Wolfe, Charles D.A.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— In 2010, Greater Manchester and London centralized acute stroke care into hyperacute units (Greater Manchester=3, London=8), with additional units providing ongoing specialist stroke care nearer patients' homes. Greater Manchester patients presenting within 4 hours of symptom onset were eligible for hyperacute unit admission; all London patients were eligible. Research indicates that postcentralization, only London's stroke mortality fell significantly more than elsewhere in England. This article attempts to explain this difference by analyzing how centralization affects provision of evidence-based clinical interventions. Methods— Controlled before and after analysis was conducted, using national audit data covering Greater Manchester, London, and a noncentralized urban comparator (38 623 adult stroke patients, April 2008 to December 2012). Likelihood of receiving all interventions measured reliably in pre- and postcentralization audits (brain scan; stroke unit admission; receiving antiplatelet; physiotherapist, nutrition, and swallow assessments) was calculated, adjusting for age, sex, stroke-type, consciousness, and whether stroke occurred in-hospital. Results— Postcentralization, likelihood of receiving interventions increased in all areas. London patients were overall significantly more likely to receive interventions, for example, brain scan within 3 hours: Greater Manchester=65.2% (95% confidence interval=64.3–66.2); London=72.1% (71.4–72.8); comparator=55.5% (54.8–56.3). Hyperacute units were significantly more likely to provide interventions, but fewer Greater Manchester patients were admitted to these (Greater Manchester=39%; London=93%). Differences resulted from contrasting hyperacute unit referral criteria and how reliably they were followed. Conclusions— Centralized systems admitting all stroke patients to hyperacute units, as in London, are significantly more likely to provide evidence-based clinical interventions. This may help explain previous research showing better outcomes associated with fully centralized models.